MOTIVASI SISWA DALAM PEMBELAJARAN TARI DI SMK NEGERI 7 PADANG: STUDI KASUS - Ayu Nara Sati; Indrayuda Indrayuda; Fuji Astuti (FBS Universitas Negeri Padang, 2017)
AbstractThis Article aims to1) to find out the reasons which cause the difference of students’ motivation in the knowledge and skill of learning dance, 2) to find out the impacts of the motivation difference toward the dance learning outcomes at class X Tari 1 of SMKN 7 Padang. The design of the research was qualitative using the descriptive analysis method. The primary instrument was the researcher herself while the secondary oneh were stationaries and a camera. There were two types of data in this research: primary and secondary data. They were obtained from library study, observation, and documentation. The data were analyzed qualitatively by observing the symptoms coming from the students’ motivation toward their knowledge and skills in learning dance. The research result shows that there are some differences of the students’ motivation related to the knowledge and skill in learning dance. There was only 1 out of 25 students who had balnce between the knowledge and skills. Meanwhile, 2 of them got higher score for their knowledge rather than their skills with a low range between them. Others tended to have low knowledge and high skills in learning dance. It happens since they alredy own the skills them selves.Keywords: Student Motivation, Dance Learning